Diversity of Cu and Total Cr Metals in Surface Water and Sludge of Textile Wastewater from Tuan Kentang Village Seberang Ulu I Sub District Palembang - Mirza Firdyah Astari; Adipati Napoleon; Risfidian Mohadi (Science and Technology Indonesia, 2018)
Nowadays, the production of rainbow fabric as a traditional fabric of Palembang city has been grown rapidly. Commonly, the wastewater as the by-product of rainbow fabric production is discharged directly to domestic channels without any previous wastewater treatment. This research was aimed to evaluate the presence of Cu and total Cr heavy metal in the area of rainbow fabric industrial center in Tuan Kentang Village, Sebrang Ulu I Sub Distric, Palembang. The Cu and total Cr polluted in the collected wastewater sample was analyzed by using atomic absorption spectrometry method with wet destruction technique. The results indicated that the area of Tuan Kentang villages is contributing metal contaminants distribution and accumulation to nature.